Existence of positive solutions for tempered fractional differential equations with p-Laplacian operator - Jiang, Jiqiang; Liu, Minghui; Liu, Lishan; Wu, Yonghong (Nonlinear Analysis: Modelling and Control, 2026)
This paper investigates the existence of positive solutions for a specific category of p-Laplacian tempered fractional differential equations in which the nonlinear term f contains an integral operator θ. By employing fixed point theorems for sum operators in partially ordered Banach spaces, together with Krasnosel’skii fixed point theorem, the existence of positive solutions is established. Moreover, iterative sequences are constructed to approximate the unique positive solution of the problem. Finally, three examples are presented to illustrate the main results.
Keywords: p-Laplacian operator; tempered fractional derivative; fractional differential equation; Krasnosel’skii fixed point theorem; fixed point theorems for a sum operator